Organizational aspects and practices for enhancing organizational project management maturity - Abdul Karim, Muhammad; Ong, Tze San; Ng, Sin Huei; Muhammad, Haslinah; Ali, Noor Azman (MDPI AG, 2022)
An organization’s performance in a project is determined by its ability to implement project management knowledge and practices. This ability reflects the organization’s level of project management maturity (PMM). PMM is premised on the belief that the higher the PMM level, the higher the ability to successfully deliver a project. With this in mind, the current paper aims to determine the type of organizational aspects and practices that could influence the success of PMM implementation in organizations. For this purpose, a systematic literature review (SLR) was performed on 23 articles published between 2011 and 2021 that studied PMM. The findings showed that most articles stressed organizational culture and integration with strategic organizational initiatives. Among all the studied industries, the information technology industry stood out. Content analysis was used for analyzing data, which were thematized using ATLAS.ti. Ten sub-themes emerged, with six sub-themes under organizational aspects and four sub-themes under organizational practices. These sub-themes, which were intertwined with the implementation and growth of PMM in organizations, positively impact project delivery performance. Based on this, several future research opportunities were proposed.